Frailty, post‐operative delirium and functional status at discharge in patients with hip fracture. (1st May 2021) - Gandossi, Chiara Maria; Zambon, Antonella; Oliveri, Giulia; Codognola, Martina; Szabo, Hajnalka; Cazzulani, Ilaria; Ferrara, Maria Cristina; Mottadelli, Chiara; Galeazzi, Marianna; Amoroso, Isabella; Zarcone, Cristina; Principato, Giulia; et al.
Abstract: Objective: To explore the effect of frailty, alone and in combination with post‐operative delirium (POD), on the risk of poor function at discharge in patients with hip fracture (HF). Methods: This is a prospective cohort study of patients with HF admitted to an Orthogeriatric Unit (OGU) between October 1, 2011 and March 15, 2019. POD was assessed using the 4AT and the Diagnostic and Statistical Manual of Mental Disorders (DSM) 5‐edition criteria. A 22‐items Frailty Index (FI) was created using the data collected on admission. The outcome measure was the Cumulated Ambulation Score (CAS) score at discharge. A log‐binomial regression model was used to assess the effect of frailty and POD on CAS. Results: A total of 988 patients (median age = 84.9 years, Interquartile range = 80.6‐89.2) were included: 360 patients (36.4%) were frail and 411 (42%) developed POD. Poor functional status at discharge (CAS score ≤2) was more common in frail than non‐frail patients (68.3% vs. 53.8%, p < 0.001) In a regression adjusted for confounders, frailty alone (Relative Risk, RR = 1.33, 95% Confidence Intervals, CI = 1.14–1.55) and POD alone (RR 1.38, 95% CI = 1.2–1.59) were associated with poor functional status at discharge; when combined, frailty and POD had an interaction, yielding a mild increase in the risk of poor outcome (RR 1.47, 95% CI = 1.28–1.69). Conclusions: In older patients undergoing HF surgery, frailty, POD and their combination, are associated with poor functional status at discharge. Key Points: Studies that investigate the joined effect of frailty and post‐operative delirium (POD) on functional outcome of hip fracture (HF) patients after surgical repair are lacking In this prospective cohort study on 988 older patients with HF, we demonstrated that frailty, POD and their combination are associated with poor functional status at discharge from an Orthogeriatric Unit Assessing frailty could help early detecting the onset of POD, promoting its prevention and reducing the negative impact on function at discharge The results of this study emphasize the need to improve geriatric knowledge across hospitals that assist older patients with HF